Estimating the Cyclically- and Absorption-adjusted Fiscal Balance for New Zealand - Miles Workman (New Zealand Government, The Treasury, 2015)
Indicators of the structural fiscal balance help inform assessments of the sustainability of fiscal settings and identify shifts in discretionary fiscal policy. The Treasury's headline structural fiscal balance indicator – the cyclically-adjusted balance (CAB) – is estimated by removing the cyclical component of the budget balance from the government's operating balance. The cyclical component is estimated by adjusting for fluctuations of actual GDP around potential GDP via the output gap. However, this approach does not take account of the composition of GDP. A boom in domestic demand – an absorption boom – will have a more pronounced impact on fiscal revenues than a boom driven by external demand (ie, net exports). This is because some components of demand are more "tax rich" than others. In particular, indirect tax revenues are closely linked to domestic demand rather than output. This paper documents the nature of the absorption cycle in New Zealand and then quantifies its effect on fiscal revenues by estimating a new structural fiscal balance indicator – the cyclically- and absorption-adjusted balance (CAAB) – over the period 1997- 2019. This indicator extends the existing CAB by adjusting for deviations in the level of domestic absorption from its long-run equilibrium level, which is in turn derived with reference to estimates of the long-run equilibrium current account balance. The estimated absorption adjustment on New Zealand's structural fiscal balance is up to 0.4 percent of GDP. This adjustment is reasonably material given conventional cyclical adjustments average 0.5 percent of GDP for New Zealand.
Keywords: E62; H62; 330; Antizyklische Finanzpolitik; Regelbindung versus Diskretion; Öffentliche Einnahmen; Bruttoinlandsprodukt; Konjunktur; Neuseeland